GeoSymbio: A hybrid, cloud-based web application of global geospatial bioinformatics and ecoinformatics for Symbiodinium-host symbioses - Franklin, E.; Stat, Michael; Pochon, X.; Putnam, H.; Gates, R. (2012)
The genus Symbiodinium encompasses a group of unicellular, photosynthetic dinoflagellates that are found free living or in hospite with a wide range of marine invertebrate hosts including scleractinian corals. We present GeoSymbio, a hybrid web application that provides an online, easy to use and freely accessible interface for users to discover, explore and utilize global geospatial bioinformatic and ecoinformatic data on Symbiodinium–host symbioses. The novelty of this application lies in the combination of a variety of query and visualization tools, including dynamic searchable maps, data tables with filter and grouping functions, and interactive charts that summarize the data. Importantly, this application is hosted remotely or ‘in the cloud’ using Google Apps, and therefore does not require any specialty GIS, web programming or data programming expertise from the user. The current version of the application utilizes Symbiodinium data based on the ITS2 genetic marker from PCR-based techniques, including denaturing gradient gel electrophoresis, sequencing and cloning of specimens collected during 1982–2010. All data elements of the application are also downloadable as spatial files, tables and nucleic acid sequence files in common formats for desktop analysis. The application provides a unique tool set to facilitate research on the basic biology of Symbiodinium and expedite new insights into their ecology, biogeography and evolution in the face of a changing global climate.